Safeguarding cancer research funding by European charities amidst the COVID‐19 pandemic - Tsagakis, Ioannis (Mol Oncol, 2020)
The COVID‐19 outbreak has affected cancer research and cancer care. European cancer charities need to reconsider strategies for safeguarding income and supporting cancer researchers, in times when sustaining cancer research funding is more crucial than ever.[Image: see text]